INNOVATIONS IN BUSINESS COMMUNICATIONS AND MANAGEMENT PROBLEMS - D. Kuzin; N. Yadova (Управленческие науки, 2016)
The article examines and systematizes the trends of the most current importance for information and business communication development, the trends having an impact on a wide range of business operations and competitiveness of contemporary business. First of all, they are technological trends (IT development) influencing information exchange and creating new forms of communications. Furthermore, they are trends of development of new marketing and relations with customers within new business areas, the development of mechanisms building up business investment attractiveness and raising strategic trust to it. It’s also the development of social media as tools of interaction with a wide range of stakeholders and consumers, as tools promoting products and services and raising consumer awareness of them.The article examines new forms of communications via social networks - crowd practices - crowd sourcing and crowd funding, which are not so widely used in Russia but are becoming more and more popular as modern communication tools. Another modern trend in communications development is examined, i. e. omni channels. Within omni channels users communicate with a company while moving freely between online or offline channels which are fully integrated with each other. This allows for maintaining a personified approach to clients and creating a reliable customer databases.Great attention in the article is paid to the sense load of contemporary business communications, becoming the means of meanings management. In particular, the concept of “Coordinated Management of Meanings” (CMM) is being studied. The concept is applied in management practice for conflict resolution and relationship management within an organization or a community.According to the authors, all of these trends are the most relevant nowadays, and it is these trends that have a critical impact on information exchange and on altering aspects of management practice in companies and other organizations as well as their competitiveness. The conclusion is quite evident: the future belongs to the developing integrated communications and communication technologies which will significantly influence the future development of management itself.